School leadership in adverse contexts - Krauel, Filomena Siqueira e Silva; Ramos, Mozart Neves (Seven Editora, 2024)
Two qualitative methods (semi-structured interviews and field research) were used to analyze the work developed by thirty-one elementary school directors from the municipal school system of Ribeirão Preto in the state of São Paulo. The result of this work reinforces the essential role of these professionals for the proper functioning of schools, while at the same time pointing out challenges that permeate the work developed by them and, not infrequently, inhibit the ability of these leaders to act successfully. These results also draw attention to the importance of developing school leaders with attributions that go far beyond administrative issues. The transformation in the role of principals implies preparing professionals capable of establishing direction for the school, developing the team, configuring a successful organizational culture, managing the educational program and the school's resources, as well as establishing a positive relationship with the external context. It is evident that in order to enable the formation of school leaders in this perspective, it is necessary that the political and technical actors that make up the education networks understand the importance of allocating efforts both to the professional development of principals and to enable adequate working conditions. Based on the evidence on the subject, this paper presents seven recommendations to support public managers in the professional development of school principals, as well as a checklist with questions to support analyses about the conditions in which they operate. DOI:https://doi.org/10.56238/sevened2024.026-036